2020
DOI: 10.1111/asj.13460
|View full text |Cite
|
Sign up to set email alerts
|

Preference for inorganic sources of calcium and phosphorus by sheep as a function of need

Abstract: Calcium and phosphorus play vital roles in the nutrition of ruminants, from DNA synthesis and intracellular communication to cell membrane fluidity and metabolic pathways (Goff, 2018; Underwood & Suttle, 1999). In turn, animals maintain a balance of minerals in their bodies that meets their nutritional needs by recognizing different internal states and discriminating among different nutrients (Provenza & Villalba, 2006). In this process, ruminants learn associations between the flavors of foods and their post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Macrominerals in livestock production systems are either added to the total mixed ratios or presented in blocks to overcome the mineral imbalance problems observed in fodder plants. Although it is not known how ruminants self-select mineral supplements, whose Ca and P concentrations vary according to the physiological state [26], these authors demonstrated that lambs were able to discriminate among minerals, and some groups modify their preferences given the influence by mineral needs which, in turn, contributes to rectify mineral imbalances.…”
Section: Mineral Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…Macrominerals in livestock production systems are either added to the total mixed ratios or presented in blocks to overcome the mineral imbalance problems observed in fodder plants. Although it is not known how ruminants self-select mineral supplements, whose Ca and P concentrations vary according to the physiological state [26], these authors demonstrated that lambs were able to discriminate among minerals, and some groups modify their preferences given the influence by mineral needs which, in turn, contributes to rectify mineral imbalances.…”
Section: Mineral Compositionmentioning
confidence: 98%
“…Sorghum is an elemental raw material in animal feed because it supplies important minerals and micronutrients that are essential for optimal health, growth, and development. Animal nutrient requirements are dynamic and depend on specific individual needs and physiological states [26]. Table 4 shows the analyzed concentration of the Sorghum bicolor Payenne mineral elements.…”
Section: Mineral Compositionmentioning
confidence: 99%